High risk of hepatic complications in kidney transplantation with chronic hepatitis C virus infection - Shih-Ting Huang; Ya-Wen Chuang; Chih-Wei Chiu; Kuo-Ting Sun; Shih-Sheng Chang; I-Kuan Wang; Brain K. Lee; Shiang-Cheng Kung; Chi-Yuan Li; Tung-Min Yu (Scientific Reports)
Abstract Data on liver issues including liver cirrhosis, hepatocellular carcinoma, and hepatic failure in renal transplant patients with HCV infection are scarce. In the present study, we conducted a large-scale population-based analysis to investigate the long-term outcomes of renal recipients with HCV infection. Propensity score matching with a ratio of 1:1 was applied. A total of 6,473renal recipients with HCV infection in case group were enrolled after PSM. Our findings showed that subjects with HCV infection in kidney transplant had significantly higher risk of hepatoma, cirrhosis, hepatic failure, and overall hepatic disease than those without HCV infection. (hepatoma: HR: 8.957; 95% CI: 5.324–15.069; cirrhosis: HR: 5.378; 95% CI: 4.363–6.631; hepatic failure: HR: 3.258; 95% CI: 2.527-4.200; overall hepatic disease: HR: 4.128; 95% CI: 3.428–4.971). In the present study, our findings show that renal recipients with HCV infection is significantly associated with a remarkably high risk of hepatic complications post-kidney transplantation.